Screen culture a global history - Butsch, Richard 1943- (Cambridge, UK Medford, MA Polity, 2019)
"Richard Butsch's expansive historical synthesis integrates social, economic, and political history to offer a comprehensive examination of screen media and screen culture globally as they have evolved through the 20th and 21st centuries. Deeply engaging, this is a masterful, integrated global history"--Provided by publisher.
Introduction: a screen culture history -- American cinema to World War One -- Global cinema, 1900-1920 -- The Hollywood studio era, 1910s-1940s -- Global Hollywood, 1920s-1950s -- Western television in the broadcast era, 1945-1990 -- Post-colonial television, 1960s-1990s -- Digital screens in the new millennium -- Using digital in the new millennium -- Globalized media in the new millennium.
Prof. Belinda Espiritu (Recommending faculty) - Bookfair 2019
Includes bibliographical references and index.
WorldShare provided record.
Keywords: Mass media -- History -- 20th century; Mass media -- History -- 21st century; History